2020
DOI: 10.1038/s41598-020-79377-w
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of endophthalmitis after intravitreal injection of an anti-VEGF agent with or without topical antibiotics

Abstract: Intravitreal injection (IVI) of anti-vascular endothelial growth factor (VEGF) is the standard treatment modality in various types of retinal diseases. However, endophthalmitis remains the most serious complication. Despite the lack of evidence that antibiotics prevent endophthalmitis, topical antibiotics are still used routinely in Japan. We conducted a retrospective multicenter study by analyzing records from patients who underwent IVI of anti-VEGF agents with or without antibiotic treatment. In the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…The endophthalmitis rates differ depending on the underlying diseases. Topical administration of antibiotics before and after intravitreal injection is not practiced in many countries, because this practice does not reduce the incidence of endophthalmitis, and also increases antibiotic resistance [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The endophthalmitis rates differ depending on the underlying diseases. Topical administration of antibiotics before and after intravitreal injection is not practiced in many countries, because this practice does not reduce the incidence of endophthalmitis, and also increases antibiotic resistance [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the injection of antibiotics into the vitreous cavity is still controversial and may even increase the risk of infection so we still exert the prevention of systemic and local antibiotics. Strict and precise control of aseptic operation is the most important preventive measure [ 50 , 51 ]. On this regard, it could be useful to develop in the near future a biodegradable deliver system to inject intravitreally the TPNS, avoiding a multiple treatment [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…26 Infectious organisms can be introduced into the eye after operative and office-based procedures such as cataract surgery and intravitreal injections. 715…”
Section: Introductionmentioning
confidence: 99%
“…20 As a result, many studies have analyzed the injection procedure to identify practice patterns that could potentially increase the risk for infection. 8,9,13,21 In particular, some have suggested that potential contamination might occur when medications are manually transferred from a packaged vial into a separate injection syringe. 22…”
Section: Introductionmentioning
confidence: 99%